Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.2 - The Product and Quotient Rules - 3.2 Exercises: 10

Answer

$J'(v)=1+\dfrac{1}{v^{2}}+\dfrac{6}{v^{4}}$

Work Step by Step

$J(v)=(v^{3}-2v)(v^{-4}+v^{-2})$ Differentiate using the product rule $J'(v)=(v^{3}-2v)(v^{-4}+v^{-2})'+(v^{-4}+v^{-2})(v^{3}-2v)'=...$ Evaluate the products and simplify $...=(v^{3}-2v)(-4v^{-5}-2v^{-3})+(v^{-4}+v^{-2})(3v^{2}-2)=...$ $...=-4v^{-2}-2+8v^{-4}+4v^{-2}+3v^{-2}-2v^{-4}+3-2v^{-2}=...$ $...=1+v^{-2}+6v^{-4}=1+\dfrac{1}{v^{2}}+\dfrac{6}{v^{4}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.